Development of an advanced tool steel for the most demanding applications in the knife industry - Rudolf, Rebeka; Ravlan, Tilen; Lojen, Gorazd; Majerič, Peter; Hudrap, Egidij (Anali PAZU, 2022)
This paper presents the starting points and an approach for the development of an advanced tool steel for the most demanding applications in the knife industry, which is carried out by SIJ Ravne Systems in collaboration with the University of Maribor Faculty of Mechanical Engineering. On one hand, the development is related to the identification of key features of tool steels that present a competitive advantage over other conventional steels, such as toughness, hardness, strength and cutting ability. On the other hand, the development also represents the implementation of appropriate technologies for the production and subsequent thermal or mechanical treatment of tool steels, in order to achieve key properties of the final products - knives.
Keywords: development; tool steel for cold work; properties; thermal and mechanical treatment; characterization